MODELING CHRONIC DISEASE PATIENT FLOWS DIVERTED FROM EMERGENCY DEPARTMENTS TO PATIENT-CENTERED MEDICAL HOMES - Diaz, Rafael (IIE Trans Healthc Syst Eng, 2015)
Chronic Disease is defined as a long lasting health condition, which can develop and/or worsen over an extended time, but which can also be controlled. The monetary and budgetary toll due to its persistent nature has become unsustainable and requires pressing actions to limit their incidence and burden. This paper demonstrates the utility of the System Dynamics approach to simulate the behavior of key factors involved in the implementation of chronic disease management. We model the patient flow diversion from emergency departments (ED) to patient-centered medical homes (PCMH), with emphasis on the visit rates, as well as the effect of insurance coverage, in an effort to assure continuity of quality care for Asthma patients at lower costs. The model is used as an evaluative method to identify conditions of a maintained health status through adequate policy planning, in terms of resources and capacity. This approach gives decision makers the ability to track the level of implementation of the intervention and generate knowledge about dynamics between population demands and the intervention effectiveness. The functionality of the model is demonstrated through the consideration of hypothetical scenarios executed using sensitivity analysis.